2006
DOI: 10.1016/j.msec.2005.10.079
|View full text |Cite
|
Sign up to set email alerts
|

Silicon made resonant microcantilever: Dependence of the chemical sensing performances on the sensitive coating thickness

Abstract: A gas sensor based on the use of a resonating microcantilever has been realized by using a polymer sensitive coating. From the theoretical study of the microcantilever sensitivity, it has been deduced that the sensitivity is enhanced when the resonant frequency or the sensitive coating thickness are increased. The sensitive coating thickness influence has then been verified experimentally by using PEUT (polyetherurethane) as sensitive coating for ethanol detection. From these measurements, some drawbacks are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 13 publications
0
16
0
1
Order By: Relevance
“…Various methods such as drop casting, [135][136][137][138] spin coating, [139,140] inkjet printing, [133] spray coating, [141,142] capillary painting, [143] plasma polymerization, [144] in situ polymerization, [145][146][147][148] grafting to via SAM functionalization, [149] and matrix assisted pulsed laser evaporation (MAPLE) [150] have been adapted for modifying MCs.…”
Section: Polymer Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods such as drop casting, [135][136][137][138] spin coating, [139,140] inkjet printing, [133] spray coating, [141,142] capillary painting, [143] plasma polymerization, [144] in situ polymerization, [145][146][147][148] grafting to via SAM functionalization, [149] and matrix assisted pulsed laser evaporation (MAPLE) [150] have been adapted for modifying MCs.…”
Section: Polymer Layersmentioning
confidence: 99%
“…Even more recently, Lochon et al have shown that the sensitivity (measured in terms of a frequency shift) of poly(etherurethane) coated MCs increases linearly with thickness of the coatings (1-20 lm). [142] However, the thermal noise of the MCs also increased significantly for MCs with the thicker coating making the detection limit to stay constant or even worsening with the increase in the coating thickness. Moreover, they have also shown that the increase in the coating thickness causes an increase in the response time, a highly undesirable output.…”
Section: Polymer Layersmentioning
confidence: 99%
“…Microcantilevers, such as those on an Atomic Force Microscope, are fabricated as a bilayer system, typically composed of silicon or silicon nitride and a chemically selective layer. 23,26,3032 These two layers have a difference in thermal expansion, which causes the cantilever to oscillate at a specific fundamental frequency, calculated using Newton's second equation of motion 30 :…”
Section: Cross-reactive Sensor Arrays For Volatiles (Crsa-v)mentioning
confidence: 99%
“…Polymers can be easily deposited and structured using spray coating [13,14], drop coating [15,16] or spin coating [17] methods. A wide range of polymers have been employed in microcantilever sensors for VOCs detection [18][19][20][21][22][23][24][25][26][27][28]. Because polymer coatings are not uniquely selective to one analyte vapor, it is typical that different polymers are used in microcantilever array for MCM analyses [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%